A Case With Apical Hypertrophic Cardiomyopathy, Multiple Coronary Artery–Left Ventricular Fistulae, and a Morphological Structure Mimicking Left Ventricular Noncompaction: Statue of Cerberus or Double-Headed Eagle?. Issue 24 (16th June 2015) - Nagumo, Sakura; Ebato, Mio; Kurata, Masaaki; Wakabayashi, Kohei; Shimojima, Hisa; Sato, Tokutada; Hori, Yoshiro; Suzuki, Hiroshi
Abstract : Supplemental Digital Content is available in the text.